Individual variation in hypoxic tolerance across athletes of different level and sport specialisations - Zelenkova, I.; Zotkin, S.; Korneev, P.; Almiashev, D.; Grushin, A.; Glazachev, O. (Gazzetta Medica Italiana - Archivio per le Scienze Mediche, 2020)
BACKGROUND: Hypoxic tolerance varies from person to person. The aim of the present study was to verify clinical hypoxic test on athletes` population across different sport specialization, training level and healthy individuals and show validity of this test on athletes` population. METHODS: The study enrolled 310 healthy individuals from 20 to 69 years of age. Subjects underwent test for acute hypoxia breathing normobaric hypoxic air (6400 m, FIO2 10.1±0.1%) till oxygen saturation (SpO2), drops down to 80%. After arterial oxygen saturation rich 80% or doesn`t rich 80% during 300 sec subject switch to the breathing with atmospheric air till SpO2 rich 96%. For the calculation of hypoxic index (I-Hyp) time of reaching 80% is divided by time of restitution to the 96% of SpO2. Test was carried out in sitting position. Oxygen saturation in blood, heart rate and minute ventilation were recorded before, during and after the test. RESULTS: Highest hypoxic tolerance has been shown in breath-hold diving in men 8.2±0.8 c.u. and woman groups 9.3±0.6 c.u. in comparison to endurance, anaerobic and motosport. Also high hypoxic tolerance has been shown in mountaineering group 6.5±0.7 c.u. In endurance athletes highest hypoxic tolerance was shown in men, cycling (2.3±0.8 c.u.) and speed skating (2.1±1.0 c.u.) groups. In woman endurance athletes speed skating 1.9± 0.9 c.u. and short track 2.0±0.5 c.u. have shown the highest values. CONCLUSIONS: Our study demonstrates a multidirectional individual dynamics of changes in arterial blood oxygen saturation in different groups of athletes. Three different types in tolerance to hypoxia were described. Hypoxic test can be used across athletic population for individual hypoxic tolerance determination.